Input spacing and the learning of L2 vocabulary in a classroom context. (September 2020) - Rogers, John; Cheung, Anisa
This study examined the optimal learning schedule for second language vocabulary within an authentic classroom setting in Hong Kong. Following a pretest, treatment, delayed posttest design, fifty-two primary school students (Cantonese first language) studied 20 English adjectives over two learning episodes under spaced-short (1-day interval) or spaced-long (8-day interval) learning conditions. The spacing of the vocabulary items was manipulated within-participants, and learning was assessed on a multiple-choice posttest, administered following a four-week delay. In contrast to previous laboratory-based findings, the results here indicated superior learning of the items presented under the spaced-short format, suggesting that lag effects might be attenuated by age, learning context and teaching procedure.